2018
DOI: 10.1080/08897077.2018.1439798
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Medication Stigma in Peer Recovery: A New Paradigm

Abstract: The community-based effort to establish and develop the AIM group demonstrates that combining the strengths of a peer support with evidence-based medication treatment is both possible and desirable. Shifting the culture of peer recovery groups to support the use of medications may have implications for improving treatment retention and should be considered as a potential strategy to reduce the burden of the opioid epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 27 publications
(38 reference statements)
1
26
0
Order By: Relevance
“…Support groups, for instance, could be a venue not only to engender social support among PWUDs but also a forum for participants to build intragroup solidarity and confront the erroneous labels perpetuated in mainstream discourse. Importantly, there are few such opportunities for PWUDs who are not in active recovery; 12-step programs like Alcoholics Anonymous (AA) and Narcotics Anonymous (NA) typically require a desire for abstinence, and even participants on MOUD report stigma in these settings (Krawczyk et al, 2018). Syringe service programs and other harm reduction sites may represent safer venues to formally or informally engage PWUDs in group-based social support without the perceived pressure of treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Support groups, for instance, could be a venue not only to engender social support among PWUDs but also a forum for participants to build intragroup solidarity and confront the erroneous labels perpetuated in mainstream discourse. Importantly, there are few such opportunities for PWUDs who are not in active recovery; 12-step programs like Alcoholics Anonymous (AA) and Narcotics Anonymous (NA) typically require a desire for abstinence, and even participants on MOUD report stigma in these settings (Krawczyk et al, 2018). Syringe service programs and other harm reduction sites may represent safer venues to formally or informally engage PWUDs in group-based social support without the perceived pressure of treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…This barrier has been observed in other studies, and often serves as a persistent deterrent to long-term OAT maintenance (Monico et al, 2015; Cooper & Nielsen, 2017). In an effort to combat this, it has been suggested that there is a need for recovery groups that recognize individuals on medication as being in recovery and destigmatize medication use to treat OUD (Krawczyk et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, OATs have been underutilized in specialty substance use programs (Krawczyk, Feder, Fingerhood, & Saloner, 2017). Other barriers include MAT stigma, long waiting lists, treatment costs, non patient-centered treatment designs, lack of access through primary care, and zero tolerance approaches (Krawczyk, Negron, Nieto, Agus, & Fingerhood, 2018; Voklow, 2014; Kourounis et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern culture surrounding opioid use disorder has also changed. Recent studies confirm that treatment for OUD is most effective when comprised of multimodal interventions that are both pharmacological and psychosocial [ 43 ]. Therefore, peer-led support groups, community-wide prevention strategies, and stigma-reducing initiatives continue to develop and to demonstrate varying degrees of success in response to the opioid epidemic [ 44 , 45 ].…”
Section: Implications For Pain Medicinementioning
confidence: 99%